2012
DOI: 10.1063/1.4768418
|View full text |Cite
|
Sign up to set email alerts
|

Metastable hydronium ions in UV-irradiated ice

Abstract: We show that the irradiation of UV light (10-11 eV) onto an ice film produces metastable hydronium (H(3)O(+)) ions in the ice at low temperatures (53-140 K). Evidence of the presence of metastable hydronium ions was obtained by experiments involving adsorption of methylamine onto UV-irradiated ice films and hydrogen-deuterium (H∕D) isotopic exchange reaction. The methylamine adsorption experiments showed that photogenerated H(3)O(+) species transferred a proton to the methylamine arriving at the ice surface, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…In the experiment performed by Lee et al, the transient mobility of excess protons in ASW was observed; a mobile proton is released from a stable hydronium structure by the external stimulus of ammonia adsorption on the ASW film surface . One might question the idling mobility of excess protons in a perfectly crystalline ice, but this would only be a hypothetical question because excess protons are almost always trapped at defects in real ice at low temperatures. ,,, There was a report about the observation of idling mobility of protons in a neutral ice I h lattice at 5 K in QENS experiments, but this claim was refuted by further investigations …”
Section: Proton Transport In Icementioning
confidence: 99%
See 1 more Smart Citation
“…In the experiment performed by Lee et al, the transient mobility of excess protons in ASW was observed; a mobile proton is released from a stable hydronium structure by the external stimulus of ammonia adsorption on the ASW film surface . One might question the idling mobility of excess protons in a perfectly crystalline ice, but this would only be a hypothetical question because excess protons are almost always trapped at defects in real ice at low temperatures. ,,, There was a report about the observation of idling mobility of protons in a neutral ice I h lattice at 5 K in QENS experiments, but this claim was refuted by further investigations …”
Section: Proton Transport In Icementioning
confidence: 99%
“…Excess protons may be generated by the photolysis of ice particles under ionizing radiation or by the injection of cosmic protons into the ice. The excess protons can be stored as hydronium ion in the ice and utilized for subsequent chemical reactions. , Moon et al proposed that such hydronium ion may act as an “invisible” acid for the reactions of interstellar ice particles. The acid–base reaction between hydronium ions and ammonia molecules trapped in the ice may explain the origin of the mysteriously large abundance of ammonium ions detected in interstellar molecular clouds.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…45 Caging and other embedding methods may potentially pave the way to better understand the fundamental aspects of activating short alkanes such as methane in the presence of water molecules in well-controlled, model systems. Moon and Kang 46 reported that the irradiation of deep UV light (10−11 eV) onto an ice film produced metastable hydronium (H 3 O + ) ions in the ice at low temperatures (53−140 K), which may lead to enhanced reactivity if other caged or sandwiched molecules coexist.…”
Section: Introductionmentioning
confidence: 99%
“…This is possible if H 3 O + is very mobile in the ice lattice or exists below the surface. 25,26 The structure shown in Figure 6(e) is informative in terms of this explanation. Because H 3 O + is formed as part of an extended H-bonded water chain, and the excess proton is mobile along the water chain with a very small barrier via the Grotthuss mechanism, 25 the impact of Cs + at low energy may only facilitate the migration of H 3 O + along the water chain, making its ejection into a vacuum very unlikely to occur.…”
mentioning
confidence: 96%